Draft Genome Sequences of Two Veillonella tobetsuensis Clinical Isolates from Intraoperative Bronchial Fluids of Elderly Patients with Pulmonary Carcinoma - Mashima, Izumi (Microbiol Resour Announc, 2019)
To date, Veillonella tobetsuensis has been known as an oral anaerobe and a facilitator of early-stage oral biofilm development with streptococci. Here, we report the draft genome sequences of 2 strains of V. tobetsuensis first isolated from intraoperative bronchial fluids of elderly patients with pulmonary carcinoma.